All Days 2013
DOI: 10.2118/167168-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Production in the Bakken Shale: South Antelope Case Study

Abstract: Focused modifications in drilling, reservoir, and completion engineering from 2009 to the present have improved Bakken, specifically the South Antelope Field, production as much as 50% to 75%. To achieve these results, Helis Oil and Gas Co., LLC formed a multi-disciplinary team in 2008 which it tasked with evaluating and overhauling its completion approach. Pre-2008 completions followed conventional wisdom: target the Middle Bakken Formation between the Lodge Pole and the Three Forks Formations. Pre-2009 wellb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The Bakken formation with multiple oil-bearing layers is one of 55 major productive tight oil reservoirs in North America (see Fig. 1) 56 [1], where Middle Bakken and Three Forks are the two primary lay-57 ers for oil production since they have the best reservoir qualities 58 such as porosity and oil saturation [2]. It has been reported that 59 the Middle Bakken has an estimated average oil resource of 3.65 60 billion barrels and Three Forks has an estimated average resource 61 of 3.73 billion barrels [3].…”
mentioning
confidence: 99%
“…The Bakken formation with multiple oil-bearing layers is one of 55 major productive tight oil reservoirs in North America (see Fig. 1) 56 [1], where Middle Bakken and Three Forks are the two primary lay-57 ers for oil production since they have the best reservoir qualities 58 such as porosity and oil saturation [2]. It has been reported that 59 the Middle Bakken has an estimated average oil resource of 3.65 60 billion barrels and Three Forks has an estimated average resource 61 of 3.73 billion barrels [3].…”
mentioning
confidence: 99%
“…The main objective of fracturing is to reconstruct the reservoir seepage formation and to achieve the purpose of the effective expansion and development of the fracture through the mechanical mechanism and provide a more efficient and convenient flow channel for the crude oil [2,7]. However, according to the evaluation of the oil production of tight reservoirs both in China and America, the production rate of tight reservoirs decreases rapidly, without a long and stable production period [2,6,[8][9][10][11]. Thus, it is difficult to obtain satisfactory oil recovery only relying on the depressurization process even with fracturing.…”
Section: Introductionmentioning
confidence: 99%
“…The Bakken formation with multiple oil-bearing layers is one of major productive tight oil reservoirs in North America [1], where Middle Bakken and Three Forks are the two primary layers for oil production since they have the best reservoir qualities such as porosity and oil saturation [2]. Figure 1 presents the location map of the Williston Basin with structure contours [3].…”
Section: Introductionmentioning
confidence: 99%